Numerical Assessment of Pipe Pile Axial Response under Seismic Excitation (Journal of Engineering, 2023)
In engineering, the ground in seismically active places may be subjected to static and seismic stresses. To avoid bearing capacity collapse, increasing the system's dynamic rigidity, and/or reducing dynamic fluctuations, it may be required to employ deep foundations instead of shallow ones. The axial aptitude and pipe pile distribution of load under static conditions have been well reported, but more study is needed to understand the dynamic axial response. Therefore, this research discusses the outputs of the 3D finite element models on the soil-pile behavior under different acceleration intensities and soil states by using MIDAS GTS NX. The pipe pile was represented as a simple elastic, and a modified Mohr-Coulomb model was used to describe the surrounding soil layers. When low acceleration was introduced in the early stages, positive frictional resistance (i.e., in dry soil, the FR was about 1.61, 1.98, and 0.9 Mpa under Kobe, Halabja, and Ali Algharbi earthquakes, respectively) was recorded. However, as the acceleration increased (from PGA = 0.1 g and 0.102 g to PGA = 0.82 g), the resistance reduced and eventually turned negative. In this study, both internal and exterior frictional resistance were measured. It was found that the soil state and acceleration intensity both have a noticeable effect on the failure process, i.e., the maximum plug soil resistance decreased by about 55% by changing the soil condition from a dry to a saturated state under the recorded data of the Kobe earthquake. A rough estimation of the long-term settlements at the shaken soil surface is meant to be included in the results of this research.